Cloud computing security for e-learning during COVID-19 pandemic - Yassen AbdelKhaleq Najm; Suray Alsamaraee; Ahmed Adeeb Jalal (Institute of Advanced Engineering and Science, 2022)
The demand for e-learning services increased during the developments of the COVID-19 virus and its rapid spread, and the recommendations of the World Health Organization (WHO) that social distancing should be required. The rapid transition to the e-learning environment quickly led to the neglect of some security aspects, which led to an increase in cyber attacks targeting computer accounts, which is one of the most important pillars of e-learning. In these papers, the attacks that target the cloud computer used in the most important e-learning have been studied and classified according to the victim using an inductive methodology based on global statistics related to cyber attacks and recent research. And suggest appropriate solutions to avoid its occurrence in the near future and raise the level of protection for those computer clouds.